Financial Feasibility Study for the Second Merchandise Store of PT Persib Bandung Bermartabat - Rahadi, Raden Aswin; Hasby Hasibuan, Muhammad Akbar; Rahmawati, Dwi; Abd. Aziz, Rozainun Haji; Damayanti, Sylviana Maya; Witdarmono, Gabriella (International Journal of Criminology and Sociology, 2022)
PT Persib Bandung Bermartabat is the company that manages a regional football team in Indonesia, the Persib Bandung Football Team. The company already has a merchandise store for the football team, but PT Persib Bandung Bermartabat needs to open a store that is suitable for Persib supporters’ desires. This study aims to discover whether or not building a new PT Persib Bandung Bermartabat merchandise store is financially feasible for PT Persib Bandung Bermartabat. As a result of this study, this project is shown to be financially feasible because this project will be profitable for the company and give a good return. The NPV of this project is positive and the Profitability Index of this project is greater than one. IRR is greater than the Cost of Capital, and Discounted Payback Period is faster than the time projection of this project. However, one thing that needs to be monitored is that the company should maintain the COGS of this project in order to make certain the COGS do not change too much from the current assumptions that are used in this financial projection. A slight change of COGS will have a big impact on the profit of this project. The company also should ensure that the Target Market Growth of this project is not less than 3,20% because it will make this project unprofitable.